Reflection and Analysis of the Training of Education Professionals for Rural Youngsters and Adults - Katia Pinheiro Freitas; Lourdes Helena da Silva (Universidade Federal do Rio Grande do Sul, 2016)
The present article addresses the challenges of training teachers for rural youngsters and adults, based on a review of the national academic literature produced from 2006 to 2011. The data, obtained from the CAPES Clearing House of Dissertations and Higher Education Institutions of Minas Gerais state, were analyzed according to the combination of the theoretical contributions from Rural Youth and Adult Education, Rural Education and Teacher Training literature. Our results reveal, among other issues, that education for rural adults and youth tends to be developed through programs and/or projects and several partnerships, particularly the involvement of social movements in the teacher training process. They also reveal the need for investment in specific teacher training - initial and continued training, based on processes that enhance the understanding of the theoretical and methodological contributions of this mode of education.